Mechanical and Microstructural Response of an Aluminum Nanocomposite Reinforced with Carbon-Based Particles - Mendoza-Duarte,José Manuel (2016)
The present work deals with the study of some aluminum (Al) composites reinforced with metallized-graphite (MG) particles prepared by mechanical milling and powder metallurgy routes. Density, morphology evolution and mechanical performance of composites were investigated as a function of MG concentration and milling time. The as-milled powders were characterized by X-ray diffraction and optical/electron microscopy; meanwhile, the mechanical testing was carried out on cylindrical specimens prepared from powders by powder metallurgy. Evidence reveals that high-energy ball milling induce a homogeneous dispersion of graphite nanoparticles in the Al matrix; this is related to an enhancement of hardness and strength response of studied composites. The composite sample with 0.5% MG addition (in weight) reached an increase of 40% on hardness and 50% on strength (compared with pure Al sample); nevertheless an adverse effect was observed with longer milling and/or higher MG concentration.